PENGUKURAN KEJAYAAN BANTUAN MODAL PERNIAGAAN USAHAWAN ASNAF DALAM KONTEKS PENCAPAIAN MAQASID AL-SHARI’AH: KAJIAN DI DAERAH KUALA TERENGGANU DAN KUALA NERUS, TERENGGANU: The Measurement of Asnaf Business Capital Assistance in the Context of Maqāṣid al-Sharī‘ah: A Study at Kuala Terengganu and Kuala Nerus, Terengganu - Marzuki, Nurmaizura; Zulkifli, Solehuddin; Wahid, Hairunnizam (Jurnal Syariah, 2019)
One type of assistance that was granted by the management and administration of zakāh to ensure that the entrepreneur recipients can improve their living standards is by assistance in the form of business capital. Capital grants are expected to generate long-term income and help to transform them to be an entrepreneur and then can also turn them to become a payer of zakāh instead of recipients. Nevertheless, it is often claimed that the assistance is not channelled effectively from the economic angle. Many beneficiaries have failed and the main reason given is a problem related to the capital. Therefore, this study was to identify factors other than capital that can influence the success or failure of the business undertaken by these entrepreneurs recipients. In order to measure the achievement of business success undertaken by these entrepreneurs recipients, the study takes into consideration two aspects of dependent variables based on income and maqāṣid al-sharī‘ah. This study used a sample of respondents from the entrepreneur recipients who received business capital assistance in the state capital of Kuala Terengganu and Kuala Nerus. A total of 140 respondents were surveyed and analyzed using analysis of regression logistic. Specifically, capital assistance has seen a modest achievement in religion, life, intellect, lineage and property. Findings shows that the success of the business conducted is influenced significantly by age and duration of trade. Hence, the important implication of this study is the finding; assessment should not focus only on the aspect of capital, but important factors that should also be included and other features.